Standardization of Honey Application on Acute Partial Thickness Wound - Raymond, Benni; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Backgrounds: : Inthe past few years, clinicians worldwide have been using honey for wound treatment. But until now, there was no such standard on method of honey application on wound. In our center, honey was applied on wound by once a day application and the result was observationally satisfactory. What if application of honey were done once every two days? Would the result become more satisfactory? This study aims to search honey application method, which gives the best result on wound treatment. Methods: This is single-blinded non-randomize clinical trial, which was conduscted in Cipto Mangunkusumo Hospital Jakarta from July until September 2012. 14 Patients with acute partial thickness wound resulted from STSG harvesting were involved in this study. Patients were devided into 2 groups: control (once every two days application of honey) and the rate of wound healing were evaluated. Rate of wound healing will be assessed as number of percentage of reduced non-epithelialized areas on the seventh day of application. Results: The mean percentage of non-epithelialized area reduction on treatment gruop was 86,76% and 97,97% on control group. There was significant difference on percentage of reduced area between control and treatment group (p<0,00). Conclusion: There was statistically signi!cant difference between once a day and once every two days application of honey. However, changing of honey dressing once a day is still a preferable method in wound treatment.